'Lighting tomorrow with today': towards a (strategic) sustainability revolution. (12th March 2010) - Nathan, Maria L.
Galbreath (2009), recognising the need for firms to more consciously link sustainability to core strategy, developed a sustainability-strategic issues framework. This article reinforces this framework by making assessment and feedback integral to the sustainable strategy process. Additional opportunities for sustainable competitive advantage through sustainability and beyond Galbreath are offered here. They are rooted in the core competencies of the firm and are made integral to the strategic management process. Galbreath is tentative as to whether the sustainability movement is like the industrial revolution in scope. This article seeks to reinforce that a revolution of just such a magnitude is at hand.